Analisis Tegangan Drop Jaringan Tegangan Rendah Dengan Metode Pembagian Beban - Suganda Suganda; Iriandi Ilyas; Sugianto Sugianto; Hendra Yulianto (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT In general, the good or bad of the distribution and distribution system of electric power is mainly in terms of the quality of the voltage received by consumers. One way to increase efficiency is to reduce power loss and minimize voltage drop on the network. The results showed that the voltage drop that occurred at the PJXS substation PT. PLN ULP Bogor Timur is caused by two main problems, the first is that the location is far from the distribution substation and around the location has high loads. Prior to the implementation of the load rupture, the magnitude of the voltage drop that occurred at the PJXS substation PT. PLN ULP Bogor Timur has passed the ideal service limit set by PT PLN Persero, which is a minimum of 10% or 198 volts from the nominal voltage of the low-voltage network, which is 220 volts. The results of this new department have a good voltage value that is not below the standard voltage drop set by PLN, namely the service voltage value has a maximum value of 5% and a minimum of 10% of the nominal voltage of 220 Volts. Keywords: Voltage drop, Low Voltage Network, Load Break